Differential Recruitment of Brain Regions During Response Inhibition in Children Prenatally Exposed to Alcohol. (11th January 2017) - Kodali, Vikas N.; Jacobson, Joseph L.; Lindinger, Nadine M.; Dodge, Neil C.; Molteno, Christopher D.; Meintjes, Ernesta M.; Jacobson, Sandra W.
Abstract : Background: Response inhibition is a distinct aspect of executive function that is frequently impaired in children with fetal alcohol spectrum disorders (FASD). We used a Go/NoGo (GNG) task in a functional MRI protocol to investigate differential activation of brain regions in the response inhibition network in children diagnosed with full or partial fetal alcohol syndrome (FAS/PFAS), compared with healthy controls. Methods: A rapid, event‐related task with 120 Go and 60 NoGo trials was used to study children aged 8 to 12 years—8 with FAS/PFAS, 17 controls. Letters were projected sequentially, with Go and NoGo trials randomly interspersed across the task. BOLD signal in the whole brain was contrasted for the correct NoGo minus correct Go trials between the FAS/PFAS and control groups. Results: Compared to the FAS/PFAS group, controls showed greater activation of the inferior frontal and anterior cingulate network linked to response inhibition in typically developing children. By contrast, the FAS/PFAS group showed greater BOLD response in dorsolateral prefrontal cortex and other middle prefrontal regions, suggesting compensation for inefficient function of pathways that normally mediate inhibitory processing. All group differences were significant after control for potential confounding variables. None of the effects of prenatal alcohol exposure on activation of the regions associated with response inhibition were attributable to the effects of this exposure on IQ. Conclusions: This is the first FASD GNG study in which all participants in the exposed group met criteria for a diagnosis of full FAS or PFAS. Although FASD is frequently comorbid with attention deficit hyperactivity disorder, the pattern of brain activation seen in these disorders differs, suggesting that different neural pathways mediate response inhibition in FASD and that different interventions for FASD are, therefore, warranted.